2017
DOI: 10.1371/journal.pone.0177132
|View full text |Cite
|
Sign up to set email alerts
|

TRPV2 knockout mice demonstrate an improved cardiac performance following myocardial infarction due to attenuated activity of peri-infarct macrophages

Abstract: BackgroundWe have recently shown that the expression of the transient receptor potential vanilloid 2 channel, TRPV2, is upregulated in the peri-infarct zone 3–5 days following an acute myocardial infarction (AMI). Further analysis has demonstrated that invading monocytes maturing to macrophages merely harbor the documented elevated expression of this channel.PurposeAssess cardiac function in TRPV2-KO mice compared to TRPV2-WT following AMI and analyze the potential involvement of TRPV2-expressing macrophages i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 30 publications
(48 reference statements)
1
31
0
Order By: Relevance
“…While several roles of TRPV2 for proper organ or cellular function have been described (11,(33)(34)(35)(36), biophysical studies on TRPV2 are scarce. The lack of selective TRPV2 agonists as well as the high heat threshold for activation hamper detailed in vitro analyses.…”
Section: Discussionmentioning
confidence: 99%
“…While several roles of TRPV2 for proper organ or cellular function have been described (11,(33)(34)(35)(36), biophysical studies on TRPV2 are scarce. The lack of selective TRPV2 agonists as well as the high heat threshold for activation hamper detailed in vitro analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The results of previous studies have demonstrated that TRPV2 has a key role in macrophage phagocytosis, and one study revealed that TRPV2 is involved in the earliest stages of phagocytosis (37,(43)(44)(45). In addition, TRPV2 functions in intra-and extracellular Ca 2+ mobilization, and it has a role in lipopolysaccharide-induced cytokine production in macrophages (46).…”
Section: Discussionmentioning
confidence: 99%
“…Although TRPV2 has been shown to be located intracellularly and translocates to the sarcolemma under stress, the effect of Tranilast does not seem to be mediated through its effects on myocytes [180]. TRPV2 is also expressed in other cell types, such as macrophages, and in fact, TRPV2 knockout improves heart performance after myocardial infarction due to attenuated activity of peri-infarct macrophages [181]. TRPV2 is also highly expressed in cardiac fibroblasts and has been shown to regulate dermal fibroblast differentiation [211].…”
Section: Trpv2 and Cardiac Fibrosismentioning
confidence: 99%